A Vision for the Future: Pathology and Emerging Treatments of Age-Related Macular Degeneration - Gleeson, Laura (Trinity Student Medical Journal, 2008)
Age-related macular degeneration impacts vastly on elderly populations, particularly in the developed world. The less severe, non-exudative form of the disease is characterised by hypopigmentation of the retina due to atrophic changes in the retinal pigment epithelium. The exudative form is caused by the formation of choroidal neovascular membranes subretinally. Trials of new treatments for the non-exudative form are currently underway and rheopheresis therapy is now available in both Canada and Germany. Treatment of the more severe exudative form has been revolutionised in the past ten years with the advent of transpupillary therapy, intravitreal steroid injections and photodynamic therapy. Most significant is the emergence of anti-angiogenic drugs pegaptanib, ranibizumab and bevacizumab. The future is hopeful, with research ongoing into genetic factors, immunotherapy and new surgical techniques also.